The Impact of the Existence of Mangrove Forests on the Social and Economic Aspects of Local Communities in the Coastal Area of Payum Merauke - Nurliah, Nurliah; Sianturi, Reny; Sajriawati, Sajriawati (Agrikan Jurnal Agribisnis Perikanan, 2025)
This research was conducted from December 2024 to January 2025. The research location was in RT 23 in the Payum coastal area, Samkai Village, Merauke Regency, with 42 respondents. The results of this study indicate that the impact of mangrove forests on the socio-economics of local communities in the Payum coastal area is divided into 2 levels of socio-economic strata, namely Lower Middle Income, namely 7 respondents or 16.67% who are in the lower middle category with an average income of IDR 36 - 60 million per year; Lower Income, namely 35 respondents or 83.33% who are in the low income category with an average income of <IDR 36 million per year. The impact of the existence of mangrove forests on the community is measured based on 3 aspects. Knowledge aspect, including the mindset and interaction of the community towards mangrove forests. Overall, the knowledge aspect has a positive impact on the existence of mangrove forests, namely with an average value of 83.32%.The attention aspect aims to measure the extent to which the community is sensitive to changes in the ecosystem in their environment. Overall, the attention aspect has a positive impact on the existence of mangrove forests, namely with an average value of 76.18%. The community perspective aspect on mangrove forest reforestation activities aims to explore actions that need to be taken to protect mangrove forests. Overall, the community perspective aspect has a positive impact on the existence of mangrove forests, namely with an average value of 76.78%.